Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis STEM Terhadap Kemampuan Berpikir Kreatif pada Pembelajaran IPAS Materi Perubahan Wujud Zat pada Siswa Kelas IV di SDN 83 Bengkulu Selatan - Nopiar Sugianto; Abdul Muktadir; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2026)
This study aims to develop a Science, Technology, Engineering, and Mathematics (STEM) based Student Worksheet (LKPD) to improve students' creative thinking skills in science learning on the Changes of State of Matter material in grade IV of elementary school. The type of research used is Research and Development (R&D) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were students of grades IV and IV of SD Negeri 83 Bengkulu Selatan. The validation results show that the STEM-based LKPD developed has a very good level of feasibility, with very valid validation results. Teachers' and students' responses to the product show a very positive category, with the assessment that the LKPD is easy to use, interesting, and encourages students to think creatively and actively in learning. The results of the effectiveness test show a significant increase in students' creative thinking skills with an N-Gain value of 0.63 which is included in the effective category. Based on these results, it can be concluded that the STEM-based LKPD is feasible, practical, and effective for use in science learning to improve the creative thinking skills of elementary school students.